557 RAREFACTION OF MYOCARDIAL LYMPHATIC VESSELS IN PATIENTS WITH CARDIAC AMYLOIDOSIS. (15th December 2022) - Aimo, Alberto; Martinelli, Giulia; Bonino, Lucrezia; Musetti, Veronica; Emdin, Michele; Pucci, Angela
Abstract: Introduction: In cardiac amyloidosis (CA), amyloid fibers accumulate in the extracellular spaces of the heart. It is reasonable to speculate that this accumulation could lead to a compression and obliteration of lymphatic vessels, and possibly to their eventual disappearance. As lympathic drainage removes proteins from the interstitial spaces, including amyloid precursors, an impairment of lympathic vessels could exacerbate amyloid accumulation, thus triggering a vicious circle. Methods: We evaluated consecutive endomyocardial biopsies (EMB) performed as part of the standard diagnostic workup for CA or for unexplained left ventricular (LV) hypertrophy, with no specific suspicion of CA. All EMBs were performed in the septal region of the LV. Three samples were analyzed through Congo red staining and immunohistochemistry, with final confirmation of the amyloid subtype through a proteomic approach. Lymphatic vessels were visualized through antibodies targeting the specific marker podoplanin. Echocardiographic variables measured at the time of the EMB were collected. Results: We examined 15 patients with CA (ATTR-CA, n=10; AL-CA, n=5; 50% men, median age 75 years [interquartile range 71-78]), and 13 patients with CA excluded (55% men, median age 68 years [59-71]). The median density of lymphatic vessels in patients with CA was 0.52 vessels/mm 2 (0-3.32), and 10.90 vessels/mm 2 (3.10-26.25) in patients without CA (p=0.001). No significant differences were found in LV mass index (p=0.170), interventricular septal thickness (p=0.262), relative wall thickness (p=0.078), or LV ejection fraction (p=0.262), while posterior wall thickness was higher in patients with CA (p=0.042). Three patients with ATTR-CA and 2 patients with AL-CA had no lymphatic vessels on their tissue samples. Patients with ATTR- or AL-CA did not display significant differences in the density of lymphatic vessels, or any metric of increased LV wall thickness or systolic function. Conclusions: We report for the first time that patients with CA have significantly less myocardial lymphatic vessels than patients without CA, despite no significant differences in the degree of LV wall thickening or LV ejection fraction. These results support the hypothesis that the lymphatic drainage is deranged in patients with CA, possibly promoting further amyloid deposition.